EDUCATION INNOVATION MODEL WITH STRATEGY IMPLEMENTATION OF THE "DARE TO BE DIFFERENT" CONCEPT - Muhammad Yusuf; Iip Syarifah; Uyu Wahyudin (Jurnal Ilmiah Teunuleh, 2021)
In the face of rapid and complex and unpredictable changes in life, educational innovation must be an important and critical priority because education is still the main support for improving the quality of human resources. The educational innovation model in the Indonesian Ministry of Education and Culture still tends to be more dominant in using a “top-down model” strategy, namely educational innovation developed from above by policy makers from the central level, to be implemented imperatively down to the lowest level of educational institutions. This will dull the creativity of the teaching staff and education staff. Thus, educational innovation should be balanced with a "bottom-up model" strategy, namely a model of educational innovation developed from below, which originates from the creativity of education personnel and educational staff in each educational institution implemented as an effort to improve the quality of education delivery. In order for educational innovation to run faster than other changes, it is necessary to look for more powerful models and strategies through various scientific approaches. The educational innovation model with a strategy of implementing the concept of "Dare to be different" is a concept used to motivate education providers to carry out educational innovations by not contradicting existing educational innovation models and strategies. This model focuses more on internalizing the enthusiasm for educational innovation, especially by educators. Dare to be different means daring to be different, so start with the word dare which stands for the words dream, attitude, relationship, and excellence.